Efficiency in Standard Penetration Test - Lukiantchuki, J. A.; Bernardes, G. P.; Esquivel, E. R. (My University, 2015)
The Standard Penetration Test (SPT) is widely used for geotechnical subsurface investigation. It provides assessment of soil properties and foundation design parameters. The Nspt index depends not only on the soil properties and the SPT setup characteristics, but also on the energy delivered to the string of rods and to the SPT sampler during the hammer impact. This paper presents the results of SPT tests performed with two instrumented subassemblies, one placed at the top and the other one at the bottom of the string of rods. This instrumentation allowed the assessment of the amount of energy transmitted to the string of rods, at sections just below the anvil and just above the sampler. Results show that the developed instrumentation is suitable to predict the amount of energy, at different sections, during the sampler penetration into to the soil. Despite the variability of the SPT setups and soil site conditions, experimental results show that SPT top and bottom efficiency values do not vary with the short and medium rod length. The SPT efficiency at a section just below the anvil was around 72% and 74% for the Bauru and Sao Carlos sites, respectively. The SPT efficiency at a section just above the sampler was around 56% and 58% for the Bauru and Sao Carlos sites, respectively.